2013
DOI: 10.2516/ogst/2012092
|View full text |Cite
|
Sign up to set email alerts
|

NMR Data Analysis: A Time-Domain Parametric Approach Using Adaptive Subband Decomposition

Abstract: and available online here Cet article fait partie du dossier thématique ci-dessous publié dans la revue OGST, Vol. 69, n°2, et téléchargeable ici Résumé -Analyse de données RMN : une approche paramétrique basée sur une décomposi-tion en sous-bandes adaptative -Dans ce papier, nous proposons une méthode rapide d'analyse de signaux de spectroscopie de Résonance Magnétique Nucléaire (RMN), dans le cas Lorentzien, fondée sur une décomposition adaptative en sous-bandes. Cette dernière est obtenue par une succession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…We observe that the proposed method performs well in the case of close and/or aligned modes. Moreover, the method proves to be competitive as compared to 2-D TLSProny [17,18] in terms of estimation accuracy and computational burden.…”
Section: -D Nmr Signal Analysismentioning
confidence: 99%
“…We observe that the proposed method performs well in the case of close and/or aligned modes. Moreover, the method proves to be competitive as compared to 2-D TLSProny [17,18] in terms of estimation accuracy and computational burden.…”
Section: -D Nmr Signal Analysismentioning
confidence: 99%
“…As shown in previous studies (Dentino, McCool, and Widrow 1978), it is found that, after implementing orthogonal transform to the input signal, the spread of its self-correlation matrix eigenvalues would decrease. Orthogonal wavelet transform has been introduced to adaptive filtering and widely applied in image and signal processing and seismic data processing (Attallah 2006;Xu et al 2007;Ventosa et al 2012;Aghayan, SiahKoohi, and Raissi 2012;Djermoune, Tomczak, and Brie 2014;Pham et al 2014). In this paper, we present the application of wavelet-domain adaptive filtering in NMR logs from tight gas sands.…”
Section: Introductionmentioning
confidence: 99%
“…A more general approach is to model the spectra in an untargeted and direct way through optimization. , In particular, time-domain signal modeling directly tackles the overlap problem and is advantageous for nonuniformly sampled data and data with baseline problems. The utility of time-domain modeling is demonstrated by CRAFT, which is the complete reduction to amplitude frequency table method. CRAFT, which is based upon a Bayesian framework, has been used to decompose 1D and 2D NMR spectra by time-domain modeling, and while CRAFT workflows can involve interactive partitioning of spectral regions, CRAFT performance is robust with respect to any user-defined parameters, and so it does have the potential for complete automation. Similar ideas have been tested by researchers including Rubtsov et al, but extensive validation and consistent workflows are not available. Singular value decomposition (SVD) and linear prediction-based methods provide alternative solutions, but the tuning parameter, namely, the reduced order, is hard to select for real-world data sets. Alternatively, global spectral deconvolution (GSD) provides a convenient commercial solution that automatically fits frequency-domain data, but in crowded regions, it tends to overfit by using many non-ideal and nonphysical peaks. Therefore, an automated untargeted method to decompose NMR spectra is still needed.…”
mentioning
confidence: 99%